2020
DOI: 10.1177/0003489420911656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender, Age, and Profound Disease on Upper Airway Stimulation Outcomes

Abstract: Objective: To evaluate treatment outcomes of upper airway stimulation (UAS) in obstructive sleep apnea (OSA) patients based on patient age, gender, and preoperative disease severity. Methods: Retrospective chart review of patients undergoing UAS from 2014 to 2018 at a tertiary care center. Data collected included demographic information, implantation records, and pre- and postoperative polysomnography (PSG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…In the study of predictors of treatment effectiveness in the ADHERE registry, for every 1 year increase in age there was a 4% increase in odds of treatment success. 37 On the other hand, in the previously quoted study by Patel et al, 49 patients above the age of 65 years had a decreased treatment response compared to their younger counterparts. Certainly, further study is warranted with regard to the ideal age for implantation.…”
Section: The Role Of Sex and Agementioning
confidence: 88%
See 1 more Smart Citation
“…In the study of predictors of treatment effectiveness in the ADHERE registry, for every 1 year increase in age there was a 4% increase in odds of treatment success. 37 On the other hand, in the previously quoted study by Patel et al, 49 patients above the age of 65 years had a decreased treatment response compared to their younger counterparts. Certainly, further study is warranted with regard to the ideal age for implantation.…”
Section: The Role Of Sex and Agementioning
confidence: 88%
“…37 Another study by Patel et al found that sex did not influence outcomes. 49 However, in the latest update of the ADHERE registry study, which included 1017 HGNS patients, female sex appeared as a significant predictor of therapy response. 50 It should be noted that given the limited morbidity associated with this therapy, HGNS may represent a very reasonable option for consideration in the aging population.…”
Section: The Role Of Sex and Agementioning
confidence: 99%
“…Pretreatment measurements were defined as polysomnography outcomes and quality of life scores obtained before HGS. Outcomes analyzed during the 12‐month postoperative period included polysomnography parameters and disease‐specific quality of life scores 18‐63 . Comparisons between pretreatment and posttreatment values were analyzed during the follow‐up period.…”
Section: Methodsmentioning
confidence: 99%